2018
DOI: 10.1002/srin.201800034
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Continuous Annealing Process Parameters on the Microstructure and Mechanical Properties of Dual Phase Steel

Abstract: Due to the difference in chemistries and manufacturing processes applied, the microstructure and mechanical properties of DP780 steel produced by different production lines may be inconsistent. Annealing experiments are designed and carried out in the laboratory based on the actual industrial production process in order to investigate the effects of continuous annealing process parameters on the microstructure and mechanical properties of DP steel quantitatively. The results show that the effect of intercritic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Our results showed that during the austenite grain refining process and the precipitation mechanisms, the presence of Nb, V, and Ti formed particles of carbides, nitrides, or a combination of both. This result, combined with the formation of precipitated carbonitrides, creates a fine dispersion in the matrix [36][37][38][39][40][41]. The presence of precipitates was confirmed by the presence of Nb, V, Ti, C, and N peaks using the XRD technique.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Our results showed that during the austenite grain refining process and the precipitation mechanisms, the presence of Nb, V, and Ti formed particles of carbides, nitrides, or a combination of both. This result, combined with the formation of precipitated carbonitrides, creates a fine dispersion in the matrix [36][37][38][39][40][41]. The presence of precipitates was confirmed by the presence of Nb, V, Ti, C, and N peaks using the XRD technique.…”
Section: Discussionmentioning
confidence: 93%
“…The vapor phase is eliminated using different cooling rates combined with polymeric solutions, directly causing boiling and convection, increasing the cooling rate. In this way, the microstructures of two-phase steel can be guaranteed [20,35,38,[40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…As a DP steel is heating up to its soak temperature, the relative proportion of ferrite to austenite will change. At the lower soak temperature, it would be expected that a lower proportion of austenite would be present leading to a lower volume fraction of martensite in the final microstructure, whilst higher soak temperatures will increase the austenite formation and subsequent martensite volume fraction in the final microstructure [18]. The light microscope images below show the initial cold-rolled microstructure in Figure 2, whilst Figure 3 shows the effect of changing soak temperature on the microstructure.
Figure 2. Initial cold-rolled microstructure before annealing.
…”
Section: Resultsmentioning
confidence: 99%
“…Increasing the intercritical temperature increases austenite formation, which can lead to an increase in the final martensite start temperature [17,18]. This start temperature is important for austenite transformation, and whether it transforms to martensite or bainite on rapid cooling [19].…”
Section: Introductionmentioning
confidence: 99%
“…Continuous annealing process is critical to the final properties during dual phase steel manufacturing [9]. The dual-phase microstructure is obtained when it is annealed within its intercritical annealing temperature range and suitably quenched.…”
Section: Annealing Experimentsmentioning
confidence: 99%